2017
DOI: 10.1038/srep41194
|View full text |Cite
|
Sign up to set email alerts
|

CuMnOS Nanoflowers with Different Cu+/Cu2+ Ratios for the CO2-to-CH3OH and the CH3OH-to-H2 Redox Reactions

Abstract: A conservative CO2-Methanol (CH3OH) regeneration cycle, to capture and reutilize the greenhouse gas of CO2 by aqueous hydrogenation for industry-useful CH3OH and to convert aqueous CH3OH solution by dehydrogenation for the clean energy of hydrogen (H2), is demonstrated at normal temperature and pressure (NTP) with two kinds of CuMnOS nanoflower catalysts. The [Cu+]-high CuMnOS led to a CH3OH yield of 21.1 mmol·g−1catal.·h−1 in the CuMnOS-CO2-H2O system and the other [Cu+]-low one had a H2 yield of 7.65 mmol·g−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…As seen in Figure3(C), the Mn 2p region consists of two peaks, Mn 2p3/2 with binding energy (BE) of approximately 643.7 eV and Mn2p1/2 with a binding energy of about 655.3 eV which are made up of Mn 4+ and Mn 3+ , indicating that Mn is in the mixed-valence state that is in Mn 3+ and Mn 4+ form 30,31,32 . For three catalysts, the Mn 3+ /(Mn 3+ +Mn 4+ ) content ratio is calculated and found that Mn 2 O 3 /CeO 2 -NP has highest Mn 4+ contents.…”
Section: Xpsmentioning
confidence: 99%
“…As seen in Figure3(C), the Mn 2p region consists of two peaks, Mn 2p3/2 with binding energy (BE) of approximately 643.7 eV and Mn2p1/2 with a binding energy of about 655.3 eV which are made up of Mn 4+ and Mn 3+ , indicating that Mn is in the mixed-valence state that is in Mn 3+ and Mn 4+ form 30,31,32 . For three catalysts, the Mn 3+ /(Mn 3+ +Mn 4+ ) content ratio is calculated and found that Mn 2 O 3 /CeO 2 -NP has highest Mn 4+ contents.…”
Section: Xpsmentioning
confidence: 99%
“…prepared Cu‐doped ZnOS oxysulfide alloy films with high hole concentration of 4.3 × 10 19 cm −3 and its applications in spintronic devices. In our previous work, Cu Ni OS, Cu In OS, Zn Ni OS, Cu Mn OS and Cu Ni SeS catalysts were synthesized for reduction of 4‐nitrophenol with NaBH 4 , reduction of Cr (VI) under dark, hydrogen evolution under lower‐power UV light, or degradation of methylene blue (MB) in the dark . Comparing with other component metals, the bimetal oxysulfide catalysts displayed excellent catalytic activity, which can be contributed to the synergistic effect between the constituents and the additional degrees of freedom to boost its catalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic chemical synthesis without the driving force of external inputs in heat, light, and electricity can be a challenge. A preliminary study on the CO 2 /MeOH/H 2 cycle by (Cu, Mn )(O,S) nanoflowers had been presented 28 . Here with lattice strain energy to replace sunlight energy as the driving force to weaken chemical bonds, our aqueous (Cu, M )(O,S) catalyst system with M = Ni, Sn, and Co is demonstrated to produce EtOH from the dissolved CO 2 and water with the C-C bond formation at normal temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…For the catalyst preparation 28 , 29 , 4.8 g cupric nitrate (Cu(NO 3 ) 2 ·2.5H 2 O) was added to a 500 ml deionized water solution, and then 3 g NiCl 2 ·6H 2 O, SnCl 2 · x H 2 O, or CoCl 2 for the second metal was mixed into the solution. After stirring for 30 min, 1.5 g thioacetamide (CH 3 CSNH 2 ) was added into the mixed solution for another 30 min stirring.…”
Section: Introductionmentioning
confidence: 99%